Sunlight mediated green synthesis of silver nanoparticles using Polygonatum graminifolium leaf extract and their antibacterial activity. (2020) - Rawat, Vanshika; Sharma, Anjna; Bhatt, Vijay Prasad; Pratap Singh, Raghvendra; Maurya, Indresh Kumar
Abstract: The present study is aimed to develop an eco-friendly method to synthesize silver nanoparticles (AgNPs) by the Polygonatum graminifolium ( P. graminifolium ) leaf extract. Synthesized AgNPs were characterized by using UV–Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and Energy dispersive X-ray spectroscopy (EDS). Resultantly, stable and green synthesized AgNPs were formulated. TEM analysis revealed the spherical shape (3–15 nm) of green synthesized AgNPs and were found efficient antibacterial activities against Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ).